THE EFFECT OF THE MARKETING MIX ON THE SALES VOLUME AT THE AIRTIRIS BRANCH OF THE AYAH BAKERY BUSINESS - Dimas Aryo Yudanto; Librina Tria Putri; Mustafa Kamal (STIE Bangkinang Publishing, 2021)
Research to determine the effect of the product, price, promotion and place on the sales volume with simulthan and partial at the Airtiris Branch of the Ayah Bakery Business. Types and sources of data used in this study are primary data and secondary data, while data collection techniques used in this study were questionnaires, file research, observation and interviews. The population in this research were all consumers at the Airtiris Branch of the Ayah Bakery Business in 2019 totaled 1.244 consumers and based on the Slovin formula, it is known that the number of samples in this research was 100 consumers at the Airtiris Branch of the Ayah Bakery Business. Data analysis was performed using multiple linear regression models. Based on the simulthan test results, the variable of the product, price, promotion and place have a significant with together effect on the sales volume at the Airtiris Branch of the Ayah Bakery Business.While based on the partial test results, the variable of the product, price, promotion and place have a significant with individual effect on the sales volume at the Airtiris Branch of the Ayah Bakery Business, with place the dominant variable affecting sales volume. The closeness of the relationship that occurs between the atractiveness of the product, price, promotion and place have a significant with individual effect on the sales volume is very strong with a correlation coefficient R of 86,9%. While contribution of the product, price, promotion and place have a significant with individual effect on the sales volume is equual to 72.9% while the remaining 27,1% is influenced by other variables not examined in this study.